2019
DOI: 10.3389/fgene.2019.00501
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Screening of the Usher Syndrome in Cuba

Abstract: Background Usher syndrome (USH) is a recessive inherited disease characterized by sensorineural hearing loss, retinitis pigmentosa, and sometimes, vestibular dysfunction. Although the molecular epidemiology of Usher syndrome has been well studied in Europe and United States, there is a lack of studies in other regions like Africa or Central and South America. Methods We designed a NGS panel that included the 10 USH causative genes ( MYO7A , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Genotype-phenotype correlations have been studied for several specific mutations, revealing similar clinical phenotype across all USH2C patients (Hilgert et al 2009). Unlike USH2A patients who display a wide variation in clinical phenotype, USH2C patients show comparatively little variation (Schwartz et al 2005). One exception is reported in a recently studied Chinese family, with three affected siblings with novel mutations in ADGRV1 (p.Gly5003fs and p.His6130fs) displaying postlingual deafness and absence of night blindness, straying from the expected USH2 phenotype (Zhang et al 2018).…”
Section: Usher Syndrome Type IImentioning
confidence: 99%
See 1 more Smart Citation
“…Genotype-phenotype correlations have been studied for several specific mutations, revealing similar clinical phenotype across all USH2C patients (Hilgert et al 2009). Unlike USH2A patients who display a wide variation in clinical phenotype, USH2C patients show comparatively little variation (Schwartz et al 2005). One exception is reported in a recently studied Chinese family, with three affected siblings with novel mutations in ADGRV1 (p.Gly5003fs and p.His6130fs) displaying postlingual deafness and absence of night blindness, straying from the expected USH2 phenotype (Zhang et al 2018).…”
Section: Usher Syndrome Type IImentioning
confidence: 99%
“…However, as our understanding of the genetic basis of USH continues to expand, this system has become increasingly insufficient to encompass the current state of knowledge. With the advent of NGS-based screening strategies, the number of causative mutations identified for each USH-associated gene has grown rapidly (Fuster-Garcia et al 2018;Wei et al 2018;Zhang et al 2018;Jouret et al 2019;Okano et al 2019;Pater et al 2019;Santana et al 2019;Qu et al 2020). This includes variants in common USH genes which result in atypical USH phenotypes, complicating the paradigm of assigning certain USH genes to either USH1, USH2, or USH3 (Pennings et al 2004;Bashir et al 2010;Pérez-Carro et al 2018;Zhang et al 2018;D'Esposito et al 2019;Valero et al 2019).…”
Section: New Directions In Usher Genotype-phenotype Classificationsmentioning
confidence: 99%
“…Genetic screening and the accurate diagnosis of Usher syndrome in different populations is necessary (Ben-Rebeh et al, 2016;Sun et al, 2018;Santana et al, 2019). Efficient molecular diagnosis of Usher syndrome in a patient's early childhood is of utmost importance, allowing better genetic counseling and therapeutic management (Ben-Rebeh et al, 2016;Ivanova et al, 2018;Maddalena et al, 2018;Jouret et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Thus, MYO7A pathogenic variants can cause both syndromic and NSHL, including autosomal dominant nonsyndromic hearing loss (ADNSHL, DFNA11), autosomal recessive nonsyndromic hearing loss (ARNSHL, DFNB2), and syndromic deaf‐blindness (Usher Type 1B, USH1B). 11 , 12 , 13 Studies have identified an interaction between the myosin VIIa protein, the SANS (encoded by USH1G gene) protein, and the harmonin (encoded by USH1C gene); this triplet in hair cell stereocilium transports the protein complex to the tip which, in turn, regulates mechanoelectrical transduction (MET). 14 , 15 The MYO7A protein contains a domain that provides its motor and cargo binding functions.…”
Section: Introductionmentioning
confidence: 99%